Hubungan Maharah al-Kalam Dengan Self-Confidence Mahasiswa PBA UIN Sunan Kalijaga - Putri Syahidah Luk Luul Jannah; Ita Rodiah (Mahira: Journal of Arabic Studies & Teaching, 2025)
This research aims to examine the correlation between maharah al-kalam (Arabic speaking skills) and the level of self-confidence among students in the Arabic Education Study Program (PBA) at UIN Sunan Kalijaga. Understanding this relationship is vital for recognizing how self-confidence impacts speaking proficiency, a core competency for future Arabic educators. A quantitative design with a correlation method was employed here. Data were collected through a questionnaire adapted from Yusuf Al Uqshaw's book on self-confidence, utilizing a 1-5 Likert scale for measurement. The analysis revealed a significant relationship (r = 0.322), indicating that higher maharah al-kalam is associated with increased levels of self-confidence among students. These findings suggest that self-confidence can enhance mastery of speaking skills. Therefore, it is crucial to integrate the development of speaking skills and self-confidence into the Arabic language curriculum, enabling educators to better support students in their learning processes and contribute to their success as future educators.